2004
DOI: 10.1177/07419325040250050201
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Emotional Disturbance Among Female Students

Abstract: This article reports data on characteristics of emotional disturbance (ED) among female students with and without ED. Teachers rated a national sample of 689 girls on the Scale for Assessing Emotional Disturbance, to measure the five characteristics of ED and a variable called social maladjustment. We compared the two categories (with ED, without ED), three school levels (elementary, middle, high), and two races (African American, European American). Girls with ED exhibited more maladaptive functioning on all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Indeed, intervention effects may reflect a gender by ethnicity interaction. Cullinan, Osborne, and Epstein (2004) posited that special education interventions and services may be more efficacious for White females with ED than their Black female counterparts with ED.…”
Section: Investigating Demographic Sampling For Studies Of Academic Imentioning
confidence: 99%
“…Indeed, intervention effects may reflect a gender by ethnicity interaction. Cullinan, Osborne, and Epstein (2004) posited that special education interventions and services may be more efficacious for White females with ED than their Black female counterparts with ED.…”
Section: Investigating Demographic Sampling For Studies Of Academic Imentioning
confidence: 99%
“…Although no gender differences for students with ED were reported in initial reading level, males with ED grew significantly faster than females with ED, on measures of letter word identification and passage comprehension. However, the authors suggested this difference in reading rate might be due to the severity of learning problems among girls with ED in light of the underidentification of girls with this designation (Cullinan, Osbourne & Epstein, 2004). …”
Section: Gender As a Moderator Of Reading Growthmentioning
confidence: 99%
“…Existing research provides some insight into the academic, social-emotional, and interpersonal functioning of females with EBD. Cullinan et al (2004), for example, used teacher ratings to assess the characteristics of females with EBD across all grade levels ( n = 218) and found that elementary females with EBD had significantly higher levels of relational problems and physical symptoms/fears compared to secondary female students with EBD. Cullinan et al also found approximately one third of their sample had comorbidity (i.e., two or more) of the five EBD criteria, indicating the needs of females with EBD may be complex and multifaceted.…”
Section: Previous Research On Females With Ebdmentioning
confidence: 99%
“…Although research has identified each of the factors detailed above as salient RPFs associated with postsecondary outcomes among youth with EBD, previous research is limited in its exploration of gender differences in these RPFs, despite variation in the prevalence and presentation of EBD for males and females (Demmer et al, 2017; Lindsay et al, 2018). Current intervention approaches assume similar RPFs for both males and females with EBD (Reddy et al, 2009) and further research is needed to discover possible gender differences in the prevalence of identified RPFs to inform tailored intervention efforts (Cullinan et al, 2004; Gage et al, 2012). In the current study, we explore gender differences in RPFs for youth with EBD based on parent, teacher, and youth reports to address the following research question: To what extent do RPFs related to postschool outcomes differ between male and female students with EBD?…”
Section: Rpfsmentioning
confidence: 99%
See 1 more Smart Citation